Does Aggressive Tax Strategy Enhance or Hinder Capital Efficiency in Financial Sector Firms - Okubokeme Derek Opudu (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study investigates whether aggressive tax planning enhances or hinders capital efficiency in the banking sector, using tax avoidance (proxied by the income effective tax rate) as the independent variable and Return on Capital Employed (ROCE) as the dependent variable. Research Methodology: This study employs a quantitative research design using panel regression analysis on selected bank data from 2014 to 2023. Key statistical measures include R-square, adjusted R-square, F-statistics, t-statistics, and Durbin-Watson statistic to test model reliability and variable significance. Results: The findings reveal a statistically significant negative relationship between tax avoidance and capital efficiency. This suggests that banks that engage in aggressive tax planning tend to experience reduced capital utilization efficiency. Conclusions: Aggressive tax planning, while potentially beneficial for short-term tax savings, may hinder banks' ability to deploy capital effectively, leading to diminished financial performance. This study emphasizes the importance of balancing tax strategies with long-term capital efficiency. Limitations: This study is limited by its reliance on the effective tax rate as a proxy for tax avoidance, a focus solely on the banking sector, and the use of publicly available data, which may not fully capture complex tax behaviors or establish causality. Contributions: This study contributes to the literature by highlighting the adverse implications of aggressive tax strategies on capital efficiency, offering insights for banks, regulators, and investors to promote sustainable financial practices within the banking sector.